Motivation of studentds to obtain technical and physical and mathematical education - Strilkova , T. (New Collegium, 2020)
The relevance of the research is due to the need to understand the views of young people on the motivation to acquire knowledge in the field of technical education and further professional activity. The paper analyses the process of interaction between students and the organization that provides educational services and ways to increase the motivation of young people to obtain technical and physical and mathematical education. The factors that influence the level of motivation during technical and physical-mathematical education are reviewed. An analysis of methods aimed at strengthening motivation to learn in modern conditions of development of Ukrainian society.The results of the analysis of the opinion of students who receive technical and physical-mathematical education on the factors that increase motivation in on each course (level) of education are presented.Methods and techniques of organization of educational process which, according to students, will allow to provide high professional qualification, opportunities for self-realization and can increase of the level of the general progress of youth are defined.Based on the results of the students survey, the structure of the influence and consequences of the process of student interaction with the organization that provides educational services is proposed. The issues of student interaction with the educational organization are covered. Recommendations for increasing the motivation of modern youth to obtain technical and physical and mathematical education are offered. The bed-rock of recommendations for increasing efficiency of the students learning process are teaching methods based on the practical application of knowledge.The results of a student survey and interviews with graduates of Kharkiv National University of Radio Electronics are presented.